Pendampingan Khitan Massal di Desa Kajan Blega Bangkalan - Abdurrohman (Jurnal Masyarakat Mengabdi Nusantara, 2022)
Circumcision is one of the teachings of Prophet Ibrahim AS which is an obligation for men. Literally, circumcision is the act of cutting or removing part or all of the foreskin of the penis. Circumcision is very beneficial for health, namely reducing the risk of urinary tract infections, overcoming phimosis, paraphimosis, balaniditis and can reduce the risk of malignancy of the penis and the spread of sexually transmitted diseases. Seeing the urgency of circumcision, during a pandemic, as well as the conditions in the midst of a coronavirus pandemic, many people were afraid to carry out circumcision and receive treatment. Therefore, a mass circumcision was carried out with the application of health protocols, which was carried out by the STIUDA Bangkalan Community Service Team. This program partners to provide free mass circumcision assistance for children in community service social service events in Kajan village during a pandemic with health protocols. The purpose of this mass circumcision social service activity is to mass circumcise Muslim children who are about to reach puberty in Kajan village, especially children who are economically disadvantaged. The method used in this activity is to disseminate information on community service activities through direct visits to foundations, social media. In other words, holding a promotion of community service activities for the Kajan village, then those who are interested register to the committee. The committee will conduct a screening for mass circumcision participants according to indications. The result of this community service activity was that mass circumcision was carried out on Sunday, March 22, 2020. It started at 08.00 - finished in the al-Mukhlishin Kajjan area. The STIUDA service team works closely with the Health Office and the surrounding community. There were 4 medical personnel involved and 2 medical assistant assistants. There were 23 participants in the mass circumcision from various hamlets in Kajan village. The conclusion of this community service has been circumcision and mass treatment of economically disadvantaged patients